LBOs’ effects on innovation: evidence from France - Le Nadant, Anne-Laure; Perdreau, Frédéric (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
Using Community Innovation Survey data from France, we provide an empirical analysis of the innovative efforts of a sample of manufacturing firms that underwent a leveraged buyout. We find no evidence that LBOs have a negative effect on firm level of innovation expenditure. In contrast, results suggest that buyouts have a positive effect on incremental innovation and that private equity firms help to make innovation spending more effective and even more efficient. It could be that private equity firms help the company to focus on its core innovative capabilities and bring innovative products to the market without increasing innovation spending.